General Training by Firms, Apprentice Contracts, and Public Policy - James M. Malcomson; James W. Maw; Barry McCormick (Center for Economic Studies and ifo Institute (CESifo), 2002)
Workers will not pay for general on-the-job training if contracts are not enforceable. Firms may if there are mobility frictions. Private information about worker productivities, however, prevents workers who quit receiving their marginal products elsewhere. Their new employers then receive external benefits from their training. In this paper, training firms increase profits by offering apprenticeships which commit firms to high wages for those trainees retained on completion. At these high wages, only good workers are retained. This signals their productivity and reduces the external benefits if they subsequently quit. Regulation of apprenticeship length (a historically important feature) enhances efficiency. Appropriate subsidies enhance it further.
Keywords: 330; general training; contract enforceability; apprenticeships; regulation